1975
DOI: 10.1002/hlca.19750580105
|View full text |Cite
|
Sign up to set email alerts
|

Selektive Funktionalisierung von Polyenen

Abstract: The possibility to functionalize selectively various polyenes using hydroboration or a Vilsmeyer‐type formylation was demonstrated. Reversible sulfur dioxide addition may be used in some cases to protect two double bonds in a polyene system. Reactions with mercuric acetate, thallium(III) nitrate, bromine or peracetic acid were found useful only in some cases for the selective introduction of functional groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 9 publications
0
18
0
1
Order By: Relevance
“…Distillation gave a colorless liquid; bp 90Ϫ92°C/ 1 Torr (ref. : [32] bp 60Ϫ62°C/0.1 Torr); n 20 D ϭ 1.5141; yield 44.0 g (87%). …”
Section: 33-trimethyl-2-[(2e)-3-methyl-24-pentadienyl]cyclohexenementioning
confidence: 99%
“…Distillation gave a colorless liquid; bp 90Ϫ92°C/ 1 Torr (ref. : [32] bp 60Ϫ62°C/0.1 Torr); n 20 D ϭ 1.5141; yield 44.0 g (87%). …”
Section: 33-trimethyl-2-[(2e)-3-methyl-24-pentadienyl]cyclohexenementioning
confidence: 99%
“…The formed solid was collected by filtration, washed with ethanol, dried and crystallized from the proper solvent. 4,6, [3,2-e] [1,2,4]triazolo [3,4- General procedure for the preparation of 3c,d…”
Section: Generalmentioning
confidence: 99%
“…The solid so-precipitated was filtered off and crystallized from benzene. [3,2-e] [1,2,3,4]tetrazolo [1,5- General procedure for the preparation of 4`a,b…”
Section: 467-tetramethyl-45-dihydrothieno[32-e][124]triazolo[mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that functionalized thiadiazines have insecticidal [2], antibacterial [3], herbicidal [4], and fungicidal [5] effects. The broad biological activities of pyrimidine [6–12] and fused pyrimidine derivatives, prompted us to synthesize new derivative of pyrimidines fused heterocycles. During last decade, we were investigating the behavior of Mannich reaction toward the multifunctional heterocyclic compounds such as 5‐mercapto‐3‐aryl‐1,2,4‐triazole (Fig.…”
Section: Introductionmentioning
confidence: 99%